Correlation between elevated serum ferritin and HbA1c in type 2 diabetes mellitus - Raj, Sumesh; Rajan, G. V. (International Journal of Research in Medical Sciences, 2017)
Background: Serum Ferritin, an acute phase reactant is a marker of iron stores in the body. Recent studies indicate that increased body iron stores and subclinical hemochromatosis has been associated with the development of glucose intolerance, type 2 diabetes, metabolic syndrome and possibly the development of diabetic retinopathy, nephropathy and vascular dysfunction. This study was carried out to examine and establish a relationship between Serum Ferritin with Type 2 diabetes mellitus and metabolic syndrome and to examine whether a correlation between S. ferritin and FBS, HbA1c exists. Methods: 86 type 2 diabetes subjects (M:F - 57:29, mean age 54.3±9.2 years, mean BMI 24.28kg/m2) which included 24 patients with metabolic syndrome were studied and compared with controls. S. ferritin, Hb, ESR, FBS, PPBS, HbA1c and fasting lipid profile were measured. Results: Serum ferritin was significantly higher in diabetic patients when compared to controls and serum ferritin had a positive correlation with increasing duration of diabetes. Conclusions: There was a positive correlation between serum ferritin and FBS, HbA1c. There was no correlation between serum ferritin and age, sex, metabolic syndrome, coexistent hypertension, total cholesterol, LDL and serum triglycerides.